Ion tracks in apatite at high pressures: the effect of crystallographic track orientation on the elastic properties of fluorapatite under hydrostatic compression - Schouwink, Pascal; Miletich-Pawliczek, Ronald; Ullrich, Angela; Glasmacher, Ulrich A.; Trautmann, Christina; Neumann, Reinhard; Kohn, Barry P. (Physics and chemistry of minerals, 2010)
Static elasticity measurements at high pressures were carried out on oriented fluorapatite single crystals, some of which contained oriented amorphous ion tracks (ITs) implanted with relativistic Au ions (2.2 GeV) from the UNILAC linear accelerator at GSI, Darmstadt. High-pressure experiments on irradiated and non-irradiated crystal sections were carried out in diamond-anvil high-pressure cells under hydrostatic conditions. In situ single-crystal diffraction was performed to determine the high-precision lattice parameters, simultaneously monitoring the widths of X-ray diffraction Bragg peaks...